PERSEPSI MASYARAKAT TERHADAP KETERBUKAAN INFORMASI PUBLIK DI KOTA SEMARANG, STUDI KASUS: Masyarakat Pengguna Pusat Informasi Publik (PIP) Tahun 2017 - Girenda Kumala Cahyaningtyas; Warsito .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Currently Semarang City government has been intensively carry out improvements to the implementation of government information towards good governance through public information disclosure is packed with good public service. This is intended to facilitate the public in obtaining various information in the information of the government. During this time, information disclosure is considered important for some people, while ordinary people sometimes take little care of it.The formation of perceptions needs to be built so that people can use the information provided by the government. Therefore, good governance is the practice or procedure of government and society managing resources to solve public problems. This study aims to explain how the public perceptions of Semarang city against public information disclosure. The method used in this research is qualitative, by doing data collection techniques using interviews, observation and literature study. Data analysis is done by data reduction phase, data presentation, verification and conclusion.The results showed that 1) Semarang City knowledge about the existence of KIP has not been fully referring to UU KIP. 2) lack of understanding of the community abaout the implementation of KIP. 3) people's assessment of KIP generally tends to require only satisfactory outcomes but does not change their behavior to participate in government. The solution to overcome this is the government is more proactive by providing intelligence to the community through innovative programs related to public information disclosure.Keywords: Good governance, Public information disclosure, Perception